1999
DOI: 10.5558/tfc75929-6
|View full text |Cite
|
Sign up to set email alerts
|

Thinking and acting differently for sustainable management of the boreal forest

Abstract: e e s h a w~ Sustainable forest management has replaced sustained yield as L'amknagement forestier durable a remplacC le rendement the new management strategy for most countries and forest soutenu en tant que nouvelle stratkgie d'amknagement pour la plucompanies. This concept has generated a lot of interest and dispart des pays et des entreprises forestibres. Ce concept a gCnkr6 cussion, and a great deal of effort is being made to modify curbeaucoup d'int66t et de discussions, et une grande partie des efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 36 publications
1
33
0
3
Order By: Relevance
“…Research in forest ecology has also shown a need to better understand processes at large spatial scales (over 100,000 ha, Hunter, 1990;Levin, 2000;Turner et al, 2001). It is difficult for forest managers to understand all the changes and possible interactions that occur over large temporal and spatial scales that exceed our first-hand perceptions (Daniels and Walker, 1996;Messier and Kneeshaw, 1999). This is even more difficult for local people who are taking part in participatory planning processes; now a normal procedure in SFM planning.…”
Section: Introductionmentioning
confidence: 98%
“…Research in forest ecology has also shown a need to better understand processes at large spatial scales (over 100,000 ha, Hunter, 1990;Levin, 2000;Turner et al, 2001). It is difficult for forest managers to understand all the changes and possible interactions that occur over large temporal and spatial scales that exceed our first-hand perceptions (Daniels and Walker, 1996;Messier and Kneeshaw, 1999). This is even more difficult for local people who are taking part in participatory planning processes; now a normal procedure in SFM planning.…”
Section: Introductionmentioning
confidence: 98%
“…Several elements, including the proportion of old forests and stand composition and structure, are currently outside their bounds of natural variability (Cyr et al 2009). It is generally accepted that significant modifications to stands can have strong impacts on biodiversity and the various natural processes of forest ecosystems (Hunter 1993, Burton et al 1999, Landres et al 1999, Messier and Kneeshaw 1999). Maintenance of biodiversity and ecological processes is crucial in order to ensure the resilience of forest stands (Drever et al 2006).…”
Section: Three Case Studiesmentioning
confidence: 99%
“…It is thought that zoning may help resolve potential conflicts through the separation of dominant uses of forests into special use areas, while allowing for the integration of biodiversity conservation with the maintenance of timber yields at the landscape level (Binkley 1997). Zoning as an approach to landscape management has been supported and contested by a number of authors (Gladstone and Ledig 1990, Vincent and Binkley 1993, Bull 1996, Hunter and Calhoun 1996, Binkley 1997, Sedjo and Botkin 1997, Messier and Kneeshaw 1999. It has been applied in numerous countries around the world including New Zealand, Australia, Malaysia, Russia, China, Guyana, and Canada.…”
Section: Zoning In the End Forest Management Approachmentioning
confidence: 99%